Considerations of a critical philosophy and christian about the globalization capitalized - Otávio Barduzzi Rodrigues da Costa (Semina: Ciências Sociais e Humanas, 2014)
This paperwork intends to trace some philosophical considerations about religion, capitalism, modernity and globalization. To this end will make a reflexive critique of the globalized world scenario and the role that religion is having this global setting. Using the ideas of authors in some quality of Assman, Hinkelammert, Ferretti among others, will show the myths by which society decides to configure globalization and the role of religion and human race in this philosophical way.